Characteristics of Polycarbonate Composites with Poly(methyl methacrylate) Grafted Multi-Walled Carbon Nanotubes - Choi, Eun Yeob; Nam, Jeong Ung; Hong, So Hyun; Kim, Chang Keun (Macromolecular research, 2018)
To improve the mechanical strength and electrical conductivity of polycarbonate (PC)-based composites with multi-walled carbon nanotubes (MWCNT), poly(methyl methacrylate) (PMMA)-grafted MWCNT (PMMA-MWCNT) was first prepared by polymerizing the monomer MMA on MWCNT that was functionalized with 3-(trimethoxysily)propylmethacrylate. A composite of PC and MWCNT was then produced by melt extrusion to examine its mechanical properties; another composite was also fabricated from solution to explore the dispersion of MWCNT and the electrical conductivity. The measured adhesion energy of the PC and PMMA-MWCNT was the highest value that could be obtained with PC and MWCNT, which guaranteed the strongest adhesion and the most uniform dispersion of the MWCNT in the composite. When compared to the PC/MWCNTs composite, the PC composite with PMMA-MWCNT exhibited improved interfacial adhesion and dispersion of the MWCNT, resulting in better mechanical and electrical properties.